Strategies and Techniques for Enhancing Fish Health and Averting Disease Outbreaks in Aquaculture Settings through the Use of Vaccination: A Review - Anusha, Mavurapu; Jagadeesh, Tejavath; Bagde, Prachi; Kumari, Pushpa; Rathlavath, Srinu; Prabhakar, Parmanand (International Journal of Bio-resource and Stress Management, 2024)
The fastest–growing animal food-producing agricultural sector in the world is aquaculture, which accounts for almost half of the world’s food fish production.However, the expansion of high-density fish populations also brings forth a challenge–the rapid transmission and spread of infectious agents including several viral, bacterial, and parasitic diseases. Expansion and successful development of sustainable aquaculture practice and increasing production largely depends upon the prevention and control of outbreaks of several emerging and re-emerging infectious diseases which can result in economic loss, food safety hazards, and environmental hazards. Vaccination strategies have become highly effective and economical in protecting the health of fish and other aquaculture organisms from various infectious diseases such as edwardsiellosis, motile aeromonas septicemia (MAS), Tilapia Lake Virus (TiLV) disease, infectious salmon anemia (ISA), vibriosis, and white spot disease etc. An ideal vaccine is expected to be safe, effective, economical, and easily administered. Most of the available fish vaccines are empirically designed vaccines based on inactivated or live attenuated bacterin vaccines. Novel advances in the fields of immunology, biotechnology, and molecular biology have led to the development in designing novel and effective fish vaccines and the improvement of the existing vaccines to provide sufficient immune protection against diseases. This review investigates the currently available fish vaccines for use in finfish aquaculture against different infectious diseases different mode of vaccine administration with addressing pros and cons in detail. The information was collected from different secondary sources, and then compiled systematically.